Digital Technology in Elementary School Mathematics Instruction: A Perspective from Public and Private Schools - Fauzi Yuberta; Pipit Firmanti; Fery Muhammad Firdaus (Universitas Pendidikan Ganesha, 2026)
The development of digital technology has become an important issue in the field of education. Therefore, evaluating the effectiveness of technology integration in learning is crucial. This study aims to evaluate the integration of digital technology in elementary school mathematics learning within the context of public and private schools. This research employed the countenance evaluation model, which includes three components: antecedents, transactions, and outcomes. Data were collected through observations, interviews, and questionnaires using observation sheets, interview guidelines, and questionnaires as research instruments. The data were analyzed descriptively and qualitatively in the form of percentages. The research subjects consisted of 316 fifth-grade students and 14 teachers from seven public schools and seven private schools. The results showed that at the antecedents stage, the use of technology was categorized as effective, supported by the availability of computers and internet access. However, policies regarding technology integration and teacher training were still limited. At the transactions stage, technology integration remained low in several schools, indicating a gap in learning practices. The use of technology had also not been optimized to support the development of mathematical concepts. At the outcomes stage, technology integration was categorized as satisfactory, as indicated by improvements in students’ academic achievement and digital skills. The implications of this study indicate the need to strengthen policies and enhance teacher training in order to optimize the integration of technology in elementary school mathematics learning.